2001
DOI: 10.1080/026520301446412
|View full text |Cite
|
Sign up to set email alerts
|

Determination of bisphenol A in canned vegetables and fruit by high performance liquid chromatography

Abstract: A high performance liquid chromatography (HPLC) method was developed for the determination of bisphenol A (BPA) that had migrated into canned fruit and vegetables. BPA was extracted with acetonitrile from the solid portion of canned food, and with an OASIS HLB cartridge from the aqueous portion, respectively. Both extracts were cleaned up on a Florisil cartridge. The HPLC separation was carried out on a Wakosil II 3C18 RS column (4.6 x 150 mm) with acetonitrile-water (40:60, v/v) as a mobile phase with a flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
3
4

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 182 publications
(96 citation statements)
references
References 7 publications
5
79
3
4
Order By: Relevance
“…The levels found in New Zealand foods are low and comparable with international results for fruits, vegetables, soups, corned beef, spaghetti, baked beans, condensed milk and soft drinks (Yoshida et al 2001, Goodson et al 2002. Canned ham, with high levels in the UK study, was not found on New Zealand supermarket shelves and levels of BPA in New Zealand meat products that might be comparable, such as tongue and luncheon, were below the LOQ in the current survey.…”
Section: Resultsmentioning
confidence: 57%
“…The levels found in New Zealand foods are low and comparable with international results for fruits, vegetables, soups, corned beef, spaghetti, baked beans, condensed milk and soft drinks (Yoshida et al 2001, Goodson et al 2002. Canned ham, with high levels in the UK study, was not found on New Zealand supermarket shelves and levels of BPA in New Zealand meat products that might be comparable, such as tongue and luncheon, were below the LOQ in the current survey.…”
Section: Resultsmentioning
confidence: 57%
“…15 Bisphenol A (BPA) with a weak estrogenic activity is widely distributed in environmental fields and biological matrices. Many HPLC methods with UV, 16 fluorescence 17,18 and electrochemical [19][20][21] detection, and with mass spectrometry, [21][22][23] have been reported for the assay of BPA in environmental and biological samples. However, most of these methods need tedious procedures such as fluorescence derivatization of BPA and off-line SPE of BPA.…”
Section: Introductionmentioning
confidence: 99%
“…These resins are used in dental fillings, food containers, plastic baby bottles, containers for mineral water storage, and food and beverage can linings. The ability of BPA to migrate from polymer to food, especially at high temperatures, has been described-for example, when canned food is heat processed or plastic dishes are used in the microwave (Brotons et al 1995;Olea et al 1996;Yamamoto and Yasuhara 1999;Yoshida et al 2001). Leaching of BPA appears to increase with repeated use of plastic products.…”
mentioning
confidence: 99%